ASPEK HUKUM PELAKSANAAN KEWENANGAN DAN KOMPETENSI BIDAN DALAM MEMENUHI STANDAR PELAYANAN KESEHATAN - Lutfiana, Indrie (Widya Aksara : Jurnal Agama Hindu, 2025)
The exercise of authority and competence by midwives is a critical component in ensuring the quality and safety of healthcare services, particularly in primary midwifery care. This study aims to analyze the legal aspects of the implementation of midwives’ authority and competence by alumni of the Bachelor of Midwifery Program in Buleleng Regency, based on prevailing regulations such as Law No. 4 of 2019 on Midwifery, Minister of Health Regulation No. 28 of 2017, and the Indonesian Midwifery Competency Standards. The research applied a normative and empirical legal approach through document analysis, semi-structured interviews, and field observations. The findings indicate that most alumni have exercised their authority and competence in accordance with regulations; however, challenges remain in the field, such as limited infrastructure, high workload, and insufficient legal awareness. These findings highlight the need to strengthen the health law curriculum in midwifery education, improve practice supervision, and promote continuous dissemination of professional regulations. This study contributes to the development of a legally compliant, safe, and professional midwifery practice governance system.